Assessment of dynamic substructuring of a wind turbine foundation applicable for aeroelastic simulations. (7th May 2014) - Damgaard, M.; Andersen, L. V.; Ibsen, L. B.
Abstract Dynamic vibration response of a wind turbine structure is examined. Emphasis is put on the dynamic interaction between the foundation and the subsoil, since stiffness and energy dissipation of the substructure affect the dynamic response of the wind turbine. Based on a standard lumped‐parameter model fitted to the frequency response of the ground, a surface foundation is implemented into the aeroelastic code FLEX5. In case of a horizontal stratum overlaying a homogeneous half‐space and within the low frequency range, analyses show that a standard lumped‐parameter model provides an accurate prediction of the frequency‐dependent foundation stiffness. The generalized stiffness matrix of the substructure is found to be in a reasonable agreement with the corresponding values based on a Guyan reduction scheme. In addition, experimental findings based on traditional and operational modal techniques on a Vestas V112‐3.3 MW wind turbine installed on drained soil clearly indicate that the energy dissipation related to the lowest eigenmode is described accurately in the aeroelastic simulation. Copyright © 2014 John Wiley & Sons, Ltd.